2021
DOI: 10.30994/jnp.v5i1.171
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Compliance With The Implementation of The Covid-19 Health Protocol In The Community of Kediri City

Abstract: Background: The implementation of the Covid-19 disease prevention health protocol is still a problem in some areas. Many police officers found violations of the Covid-19 prevention health protocol. There are indications that the behavior of the Indonesian people is not ready to face the covid-19 outbreak, which is characterized by four types of behavior, one of which shows non-compliance.Purpose: This study aimed to examine what are the most dominant determinants of knowledge, anxiety, age, gender, and persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Another study found that social norms and social models significantly affect commitment (p < 0.001) (Sanaeinasab et al, 2012). Sari and Fawzi (2021)'s study in Indonesia about adherence to health protocols showed that knowledge was significantly related to people adherence (p = 0.000). Also, the community felt the support of good community leaders (64.2%) (Wiranti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that social norms and social models significantly affect commitment (p < 0.001) (Sanaeinasab et al, 2012). Sari and Fawzi (2021)'s study in Indonesia about adherence to health protocols showed that knowledge was significantly related to people adherence (p = 0.000). Also, the community felt the support of good community leaders (64.2%) (Wiranti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Webster et al's (19) study showed that factors such as public awareness of disease and quarantine procedures, social norms, perceived benefits of quarantine and understanding of disease risk, as well as practical issues such as resource depletion or financial consequences of unemployment are related to the degree of observing quarantine (19). In a study conducted in Indonesia, the variables of knowledge, personality and concern were reported as important determinants of observing health protocols related to COVID-19 (20). In a review study conducted by Shushtari et al (17), living and working conditions, social support, trust, social norms, economic and social status, and mental health were reported to be the most important social determinants of following the COVID-19 health protocols.…”
Section: Introductionmentioning
confidence: 99%
“…By R. K. Sari (2021) for the treatment of bruises in the Serawai tribe, the leaves of Peronema canescens, Jack (Sungkai Leaf) are crushed into pieces. A district in Jambi Province, namely Merangin, uses a decoction of sungkai leaves as one of the traditional plants given to patients suffering from Covid-19.…”
Section: Introductionmentioning
confidence: 99%